2007
DOI: 10.3844/ajavsp.2007.23.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short or Long Term FGA Treatment with or without eCG on Reproductive Performance of Ewes Bred Out-of-season

Abstract: Abstract:The objective was to evaluate the effects of intravaginal FGA sponges inserted for 4 or 12 days with or without eCG on reproductive performance of ewes out-of-season. Forty-eight anestrous ewes were assigned in equal numbers to four treatments in a 2x2 factorial design. Ewes were administered with FGA sponges on May 17 for 12 days (12-day-FGA-eCG and 12-day-FGA groups, n= 12 each) and on May 25 for 4 days (4-day-FGA-eCG and 4-day-FGA groups, n= 12 each). All treatments were timed to end together on Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
6
8
0
1
Order By: Relevance
“…The lambing rate in the differently treated ewes was 61.5, 88.5 and 92.3%, respectively. The results of the present study are compatible with the study results of Santos et al (2010) who demonstrated that short-term progestagen treatment does not improve the fertility of ewes, as was previously reported (Husein et al, 2007;Ustuner et al, 2007;Amer and Hazzaa, 2009). In the present study, the multiple birth rate and litter size in the treatment groups were lower than the values observed in hormone treated native ewes of Turkey (Askin, 1988;Koyuncu and Yerlikaya, 2007;Karaca et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…The lambing rate in the differently treated ewes was 61.5, 88.5 and 92.3%, respectively. The results of the present study are compatible with the study results of Santos et al (2010) who demonstrated that short-term progestagen treatment does not improve the fertility of ewes, as was previously reported (Husein et al, 2007;Ustuner et al, 2007;Amer and Hazzaa, 2009). In the present study, the multiple birth rate and litter size in the treatment groups were lower than the values observed in hormone treated native ewes of Turkey (Askin, 1988;Koyuncu and Yerlikaya, 2007;Karaca et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…Based on physiology of exposure to progestagens compared to long-term exposure. Our results are in accordance with others, where short treatments combined with natural mating resulted in higher (Viñoles et al, 1999) or equal (Ungerfeld and Rubianes, 1999;Ataman et al, 2006;Housein et al, 2007) pregnancy rate, during the breeding or anoestrous season, respectively, compared to long treatment. Recently, Martemucci and D'Alessandro (2011), shown that FGA-PGF2α-eCG short-term (5-days) treatments could be used as a valid alternative to FGA-eCG long-term protocol for synchronization of oestrus after natural mating during the breeding season.…”
Section: Discussionsupporting
confidence: 82%
“…In the end, however, a subluteal effect may happen and decrease the speed of follicular renewal (Hamra et al, 1986). The use of progestagen during a short time would be an alternative solution because it could improve estrus synchronization in ewes (Husein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%